2011
DOI: 10.4195/jnrlse.2010.0006u
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles among Students in an Advanced Soil Management Class: Impact on Students’ Performance

Abstract: Learning styles represent an integral component of the learning environment, which has been shown to differ across institutions and disciplines. To identify learner preferences within a discipline would aid in evaluating instructional resources geared toward active learning. The learning profiles of second‐year soil science students (n = 62) were investigated using the VARK and index of learning styles (ILS) questionnaires, at the mid‐semester stage. Student performance was measured using quality points (cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Some studies have also been made to identify the relationship between VARK learning style preferences and student performance in university courses. For example, [13] found that a strong kinesthetic learning style had a significant negative relationship with performance in physiology courses among a sample of 64 students; but [14] found no significant relationship between VARK learning style preferences and course performance among a sample of 62 students studying soil management science. Other studies by [15] used the VARK inventory to assess the relationship between student learning styles and their performance among 211 students from a mix of introductory microeconomics and introductory macroeconomics courses.…”
Section: Vark Learning Stylementioning
confidence: 99%
“…Some studies have also been made to identify the relationship between VARK learning style preferences and student performance in university courses. For example, [13] found that a strong kinesthetic learning style had a significant negative relationship with performance in physiology courses among a sample of 64 students; but [14] found no significant relationship between VARK learning style preferences and course performance among a sample of 62 students studying soil management science. Other studies by [15] used the VARK inventory to assess the relationship between student learning styles and their performance among 211 students from a mix of introductory microeconomics and introductory macroeconomics courses.…”
Section: Vark Learning Stylementioning
confidence: 99%
“…1). This result suggests that these types of activities appeal to students in a course designed for environmental science majors and provides further support for the prevalence of the kinesthetic learning style among undergraduate soil science students (Eudoxie, 2011). However, only one of these three hands‐on lecture tutorials helped the students to significantly improve their quiz scores.…”
Section: Resultsmentioning
confidence: 53%
“…This trend is troubling when we consider that well‐trained soil scientists have an important role to play within the scientific community (Hartemink and McBratney, 2008). Past research on learning styles in a Soil and Water Management course suggests that the majority of students in this type of course are multi‐modal or kinesthetic learners (Eudoxie, 2011). Based on the diversity of learning styles in a typical soils class, it is important to provide students with a wide variety of learning tools that will work for different learning styles.…”
mentioning
confidence: 99%
“…Learning styles, also known as cognitive styles or learning preferences show how students prefer ways of learning [1] [2] and are characteristic behaviors that tend to be relatively stable over time [1]. Learning style is defined as a person's natural way, one's habits and something more suitable for someone in absorbing, processing and mastering new information and skills [3] and is an integral component of the learning environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Student learning styles are important cognitive characteristics that influence the way of learning. However, research conducted by Eudoxie confirms that the learning outcomes of students in the face-to-face learning model are influenced by student learning styles [4]. When learning styles match the learning methods used, better learning outcomes will be obtained, but on the contrary when learning styles and learning methods do not match, learning outcomes significantly deteriorate [8].…”
Section: Introductionmentioning
confidence: 99%